Evaluation of the D.C. Superior Court Drug Intervention Programs - Adele Harrell, Shannon Cavanagh, and John Roman (My University, 2016)
An evaluation of the impact of two D.C. Superior Court experimental interventions on drug-involved defendants in Washington. During the experiment, all drug felony defendants were randomly assigned to one of three dockets established to expedite the handling of drug cases. One drugcase docket intervened in the standard manner. Another docket intervened through a new comprehensive treatment program. The third offered an experimental program mandating a graduated schedule of sanctions if the defendant failed compulsory drug tests.